A Systematic Review and Meta-Analysis of Randomized Trials to Evaluate the Impact of Exercise on Heart Rate Variability Post-Bariatric Surgery - Bitencourt, Tulio H. B. [UNESP] (2024)
Bariatric surgery is an approach used to treat patients with obesity in a small minority of eligible patients. Non-pharmacological therapies are important to maintain decent health status post-bariatric surgery. We performed a systematic review with meta-analysis to evaluate the effects of exercise on heart rate variability (HRV) in patients submitted to bariatric surgery. The searches were made via MEDLINE/PubMed (via the National Library of Medicine), EMBASE, Web of Science, and Scopus databases. We included non-blind, single-, or double-blind randomized control trials in patients older than 18 years of age submitted to bariatric surgery. The intervention group should be submitted to an exercise training protocol, including aerobic, strength, and other exercise modality after bariatric surgery. We documented 245 studies, and after screening and eligibility phases, only 4 were included. We observed no significant change for the SDNN: subtotal = 19.74 (CI: −4.98, 44.45), p = 0.12, I2 = 85% (very low quality of evidence); pNN50: subtotal = 13.09 (CI: −9.17, 35.35), p = 0.25, I2 = 93% (very low quality of evidence); RMSSD: subtotal = 8.44 (CI: −3.61, 25.50), p = 0.17, I2 = 95% (very low quality of evidence); SD1: subtotal = 9.36 (CI: −4.48, 23.21), p = 0.19, I2 = 96% (very low quality of evidence). We could not detect significant effects of exercise on resting HRV after bariatric surgery. The low certainty of the results via the evidence level analysis suggest further studies might be beneficial.